2023
DOI: 10.1152/ajpheart.00023.2023
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic vessels and the renin-angiotensin-system

Abstract: The lymphatic system is an integral part of the circulatory system and plays an important role in the fluid homeostasis of the human body. Accumulating evidence has recently suggested the involvement of lymphatic dysfunction in the pathogenesis of cardio-reno-vascular (CRV) disease. However, how the sophisticated contractile machinery of lymphatic vessels is modulated, and possibly impaired in CRV disease, remains largely unknown. In particular, little attention has been paid to the effect of the renin-angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 262 publications
0
3
0
Order By: Relevance
“…24 While precise measures of such contractility in humans are lacking due to ongoing challenges in lymphatic imaging, 25 studies in spontaneously hypertensive rats recently revealed an impaired collecting lymphatic vasomotion profile 26 and decreased endotheliumdependent and endothelium-independent relaxation of the thoracic duct 27 was not observed in young rats and its development was prevented by antihypertensive treatment. 27 These findings suggest an impact of (long-standing) hypertension, of hypertensive mediators (like Ang II 15 ), and possibly antihypertensive drugs 28 on lymphatic contractility, but leave the question of a dysfunctional lymphatic system as a determinant/perpetuator of salt-sensitive hypertension and hypertensive organ damage unanswered.…”
Section: The Lymphatic System: Anatomy and Mechanicsmentioning
confidence: 99%
“…24 While precise measures of such contractility in humans are lacking due to ongoing challenges in lymphatic imaging, 25 studies in spontaneously hypertensive rats recently revealed an impaired collecting lymphatic vasomotion profile 26 and decreased endotheliumdependent and endothelium-independent relaxation of the thoracic duct 27 was not observed in young rats and its development was prevented by antihypertensive treatment. 27 These findings suggest an impact of (long-standing) hypertension, of hypertensive mediators (like Ang II 15 ), and possibly antihypertensive drugs 28 on lymphatic contractility, but leave the question of a dysfunctional lymphatic system as a determinant/perpetuator of salt-sensitive hypertension and hypertensive organ damage unanswered.…”
Section: The Lymphatic System: Anatomy and Mechanicsmentioning
confidence: 99%
“…Additionally, renin and angiotensin II, typically found in interstitial fluid, are also present in kidney lymph. Intriguingly, their concentrations in renal lymph might surpass those in venous plasma, hinting at a possible secretion of these substances into the kidney’s interstitial space [ 52 , 53 , 54 ]. However, the specific role of lymphatic transport in these molecules remains uncertain.…”
Section: Kidney Lymphatic Systemmentioning
confidence: 99%
“…The role of the renal lymphatic system is pivotal across various facets of kidney function, including kidney development, immune responses, tissue fluid regulation, and maintaining fluid balance. Furthermore, it significantly influences the progression and persistence of renal ailments [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. In adult kidneys, lymphatic capillaries are predominantly situated near glomeruli and tubules within the renal cortex, while classical lymphatic channels are not typically present in the renal medulla of healthy kidneys.…”
Section: Renal Lymphatic System Dysfunctionmentioning
confidence: 99%